Hugo's haunted handbook - Whamond, Dave (Owlkids Books, 2024)
"Got ghosts? Then you've come to the right book! Hugo is a ghost expert, and he can tell you exactly how to boot out your boo. After all, he got rid of his ghost, no problem! He knows everything there is to know about ghosts, he has the proper ghost-hunting equipment, and he can offer five handy tips to remove your ghost forever. But has Hugo really gotten rid of his ghost? And are ghosts really that scary? Would it be so bad to keep a ghost around? They might actually be good company if you just give them a chance ... A silly, laugh-out-loud graphic novel for very young readers that breaks the fourth wall. It's a lighthearted look at friendship and the meaning of true companionship. The relationship between Hugo and his ghost is irresistible. The reader watches Hugo deny his friendship with his ghost for the purpose of writing his Haunted Handbook about how to get rid of a ghost, until he finally succumbs and realizes the value of the camaraderie the two of them share."--